Cambodia : Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report, 2006)
Cambodians have displayed tremendous resilience. The National Strategic Development Plan (NSDP) has been formulated using the comprehensive Rectangular Strategy of the Royal Government of Cambodia and synthesizes the Cambodia Millennium Development Goals (CMDG), the National Poverty Reduction Strategy (NPRS), et cetera It provides the framework for growth, employment, equity, and efficiency to reach CMDGs. It lays out the vision, goals, strategies, and priority actions. Its implementation will be regularly monitored to make annual adjustments. NSDP could be successfully implemented to attain intended goals and reduce poverty.